FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI DALAM MENGIKUTI PROGRAM ASURANSI USAHATANI PADI (AUTP) DI KABUPATEN TANJUNG JABUNG TIMUR - Hardiana, Juli; Elwamendri, Elwamendri; Sri Nurchaini, Dewi (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2019)
This research was conducted with the aim of (1) to know the description of rice field farming in East Tanjung Jabung Regency, (2) to know the factors that influence the farmer's decision in following the rice insurance program (AUTP) program in Tanjung Jabung Timur Regency. The selection of this location is done purposively (Purposive) with the consideration that Simpang Datuk Village is the source of its livelihood from rice field farming activities and has the largest number of farmer groups and one of its paddy rice fields following the rice insurance (AUTP) program in Tanjung Jabung Timur Regency. Method of sampling using simple random sampling (Simple Random Sampling) with the number of respondents as much as 78 farmers. Data analysis using descriptive analysis method, then use logistic binery analysis. It can be seen from the general description of the farming activities in the research area that is the use of farming production factors is that the widest use of land ranges from 1.6 to 20 Ha, for the use of labor both in the family and outside the family ranges from 84 to 120 HOK while for capital used in farming activities ranges from Rp 3.305.715 - Rp 3.795.100. Thus all factors used in farming activities affect the productivity in achieving the expected results of farmers. Factors that are expected to affect farmers' decision to participate in the AUTP program include the ability of farmers to pay premium / income, experience of farming, the area of ​​land owned, the number of dependents of the family and the occupation of farmers. The results showed that there were 4 factors with error rate (5%) which significantly influence the decision to follow AUTP program in Simpang Datuk Village, Nipah Panjang Sub-District, Tanjung Jabung Timur Regency. Factors in question is the ability of farmers to pay premium / income, experience berusahatani, land owned, and the number of family dependents. While side job variables have no significant effect on farmer's decision in following program of insurance of paddy farming (AUTP) in East Tanjung Jabung Regency. Keywords: Factors, Decisions, AUTP Programs.